THE VULNERABILITY OF THE ACADEMIES SERVICES AND CONGENERS TO BENEFICIARY, BY THE LAW Nº. 15.619 / 2015 OF THE STATE OF PERNAMBUCO/BRAZIL. (Fiep Bulletin - online, 2016)
This article aims to demonstrate the vulnerability of the beneficiary at the Annual Law of the State of Pernambuco No. 15,619 / 15, due to the college offer the Professional Physical Education in performing physical assessment, functional and medical history, making it mandatory to fill Form (PAR-Q) and having implications when completing, signing the liability waiver. Throughout the academic approach, escoimada in robust legal and doctrinal guidance, evidence of which is an obligation "ex officio" the physical education professional to undertake Beneficiary Assessment, under penalty of ethical, civil and criminal liability, taking you, the business premises where he develops his working activities and, as a consumer relationship, the vulnerable conditions, if any sudden illness, solidarity, there will be accountability with reversal of the burden of proof, in favor of the beneficiary and to the detriment of the Establishment of the offerer Professional service and that did not perform the Physical Evaluation, all before the Judiciary and class organ. The protection of society, the beneficiary and the Physical Education Professional is found in obedience to kind of their profession, which guides you to make the Physical Evaluation in the recipient, thus optimizing the redirection of planning and expected results, ensuring that way, the society.
Keywords: Assessment. Liability. Benefits.